Redescription of a poorly known soft scale insect, Pulvinaria ixorae Green (Hemiptera: Coccomorpha: Coccidae) from India, with biological notes and a new distribution record - Das, Anirban; Ravindranath, Nihal; Ravi, Gollapelly; Pramanik, Aniruddha; Das, Bijan Kumar (Zootaxa, 2026)
Pulvinaria ixorae Green, 1909 is a soft scale insect (Hemiptera: Coccomorpha: Coccidae) originally described from Sri Lanka and later recorded from other parts of the Indian subcontinent, but its diagnostic characteristics, distribution, and ecology remain inadequately documented. In the present study, the adult female of P. ixorae is redescribed in detail, based on fresh specimens collected from Odisha, India, and is illustrated from slide-mounted specimens, to facilitate accurate identification and to distinguish it from other closely related members of Pulvinaria. Ecological observations are also given, including the host-plant association, a predatory natural enemy (Jauravia sp., Coleoptera: Coccinellidae), and the relationship between P. ixorae and an attendant ant. The redescription and new information provide a better understanding of the taxonomy and ecology of this potentially economically important soft scale species.